Haemoparasites—Challenging and Wasting Infections in Small Ruminants: A Review - Stuen, Snorre (Animals (Basel), 2020)
SIMPLE SUMMARY: Vector-borne haemoparasites in small ruminants are widespread, although only scattered information is available on their occurrence. Haemoparasites occur in the genera Anaplasma, Babesia, Ehrlichia, Mycoplasma, Theileria and Trypanosoma, of which several species cause challenging and wasting conditions with severe impact on the small ruminant industry. However, the controls of these infections are challenging tasks, especially since several of the available medical drugs have negative environmental consequences. In addition, vectors may spread across the world to new geographical areas, especially related to climate change and increased globalization. These changes may have a profound impact on infection ecology and disease management. Integrated control strategies should be implemented, such as breed resistance against vectors and infections, and strategic vector and infection control. ABSTRACT: Haemoparasites include bacteria, mycoplasma, protozoa and flagellates inhabiting the bloodstream of living hosts. These infections occur worldwide and are transmitted by vectors, especially ticks and tsetse flies. Geographical distribution varies due to movements of animals and vectors between geographical areas, and even between countries and continents. These changes may be caused by climate change, directly and indirectly, and have a huge effect on the epidemiology of these microbes. Active and ongoing surveillance is necessary to obtain reliable maps concerning the distribution of these infections in order to do proper risk assessment and efficient prophylactic treatment. Genera Anaplasma, Ehrlichia, Mycoplasma, Babesia, Theileria and Trypanosoma include common haemoparasite species in small ruminants causing a variety of clinical manifestations from high fatality rates to more subclinical infections, depending on the species or strain involved. These infections may also cause ill-thift or long-lasting wasting conditions. Life-long infections are a common feature of these pathogens. The present review will focus on haemoparasites in small ruminants, especially related to challenging and wasting infections.